2021
DOI: 10.1002/oa.2939
|View full text |Cite
|
Sign up to set email alerts
|

“I wanna be your dog”: Evaluating the efficacy of univariate and multivariate methods for differentiating domestic and wild canids in North America

Abstract: The domestic dog (Canis familiaris) holds a unique place in human cultures as the first species to be domesticated and has been adapted to a greater diversity of functions requiring far greater morphological variation than any other domesticate. Because of this variability in morphology and pronounced skeletal similarities with other canid species, dog remains are frequently challenging to identify in the archaeological record. Analysts have attempted to overcome these challenges by proposing a diverse array o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Sheep and goat long bones are also difficult to differentiate [ 29 , 68 ]. Domestic dogs pose many issues, not just because of their similarity to other canids included in this study (e.g., coyotes and wolves) [ 69 , 70 ] but also because of their high degree of variability in both morphology and size [ 71 , 72 ]. The DFA species classification rates were significantly higher than chance, but the probability of species misidentification remains relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep and goat long bones are also difficult to differentiate [ 29 , 68 ]. Domestic dogs pose many issues, not just because of their similarity to other canids included in this study (e.g., coyotes and wolves) [ 69 , 70 ] but also because of their high degree of variability in both morphology and size [ 71 , 72 ]. The DFA species classification rates were significantly higher than chance, but the probability of species misidentification remains relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous attempts to standardize identification of canids based on cranial and dental differences over the years (e.g., Ameen et al 2017;Andersone and Ozolins 2000;Benecke 1987;Bockelmann 1920;Clutton-Brock 1963;Germonpré et al 2015;Morey 1994;Olsen and Olsen 1977;Studer 1901). However, recent reviews and morphometric studies of these collected methods concluded that many measurements used for differentiation show a great deal of variation within modern and archaeological dog, wolf, coyote, and fox specimens (Janssens et al 2019;Welker et al 2020). A mulitvariate approach is best for distinguishing dogs from other canids, and in this case the ratio of M1 length to mandibular bowing in the TCT dog specimen was compared to the measurements of the same presented in Welker et al (2020).…”
Section: Comparative Cranial and Dental Analysismentioning
confidence: 99%
“…However, recent reviews and morphometric studies of these collected methods concluded that many measurements used for differentiation show a great deal of variation within modern and archaeological dog, wolf, coyote, and fox specimens (Janssens et al 2019;Welker et al 2020). A mulitvariate approach is best for distinguishing dogs from other canids, and in this case the ratio of M1 length to mandibular bowing in the TCT dog specimen was compared to the measurements of the same presented in Welker et al (2020). While the TCT dog specimen's left M1 length of 13.66 mm and mandibular bowing angle of 17.17° falls outside the significant cluster (95% CI) of domestic dog measurements presented by Welker et al (2020), it does closely correspond to several samples within their dataset which belong to both Chihuahua and toy sized mixed breed dogs (Welker et al 2020).…”
Section: Comparative Cranial and Dental Analysismentioning
confidence: 99%